PERBANDINGAN REKSADANA SYARIAH DENGAN REKSADANA KONVENSIONAL DALAM DUNIA PERBANKAN - Reonika Puspita Sari (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Low risk investments almost all investors want to do it and vice versa, it is not easy to find investors who want to do it. Many alternatives to invest for investors one way through a mutual fund..The difference between Islamic mutual fund and conventional mutual fund is based on the legal basis, that sharia mutual fund is based on Islamic Shari'a, all of its elements are more to see halal and haramnya while conventional mutual funds more to the public do not look halal and haramnya in a company that produce a goods that will investing funds into these mutual funds. Thus, it can be concluded that, Islamic mutual funds in the investment not only aims to get a high return and not only maximize the high welfare of the owners of capital, but more attention to the portfolio owned remains on the investment aspects of companies that have halal and good products which do not violate the rules of sharia, while conventional funds only aimed as maintenance of money that is in the guard or maintained and not based on Islamic Shari'ah not prioritize maslahahnya but only prioritize the benefits alone.